Glucose uptake by the brain on chronic high-protein weight-loss diets with either moderate or low amounts of carbohydrate. Issue 4 (28th February 2014) - Lobley, Gerald E.; Johnstone, Alexandra M.; Fyfe, Claire; Horgan, Graham W.; Holtrop, Grietje; Bremner, David M.; Broom, Iain; Schweiger, Lutz; Welch, Andy
<x content-type="archive" xml:space="preserve">Abstract</x> Previous work has shown that hunger and food intake are lower in individuals on high-protein (HP) diets when combined with low carbohydrate (LC) intakes rather than with moderate carbohydrate (MC) intakes and where a more ketogenic state occurs. The aim of the present study was to investigate whether the difference between HPLC and HPMC diets was associated with changes in glucose and ketone body metabolism, particularly within key areas of the brain involved in appetite control. A total of twelve men, mean BMI 34·9 kg/m2, took part in a randomised cross-over trial, with two 4-week periods when isoenergetic fixed-intake diets (8·3 MJ/d) were given, with 30 % of the energy being given as protein and either (1) a very LC (22 g/d; HPLC) or (2) a MC (182 g/d; HPMC) intake. An 18fluoro-deoxyglucose positron emission tomography scan of the brain was conducted at the end of each dietary intervention period, following an overnight fast (n 4) or 4 h after consumption of a test meal (n 8). On the next day, whole-body ketone and glucose metabolism was quantified using [1, 2, 3, 4-13C]acetoacetate, [2, 4-13C]3-hydroxybutyrate and [6, 6-2H2]glucose. The composite hunger score was 14 % lower (P= 0·013) for the HPLC dietary intervention than for the HPMC diet. Whole-body ketone flux was approximately 4-fold greater for the HPLC dietary intervention than for the HPMC diet (P< 0·001). The 9-fold difference in carbohydrate intakes between the HPLC and HPMC dietary interventions led to a 5 % lower supply of glucose to the brain. Despite this, the uptake of glucose by the fifty-four regions of the brain analysed remained similar for the two dietary interventions. In conclusion, differences in the composite hunger score observed for the two dietary interventions are not associated with the use of alternative fuels by the brain.